Free spirit : growing up on the road and off the grid - Safran, Joshua (Hyperion, 2013)
Tells the harrowing, yet wryly funny story of Safran's childhood chasing the perfect life off the grid--and how he and his mother survived the imperfect one they found instead. More than just a coming-of age story, "Free Spirit" is a journey of the spirit, as Safran reconnects with his Jewish roots; a tale of overcoming adversity; and a captivating read about a childhood unlike any other.